In Vitro Genotoxic Effects of Zerumbone and Cisplatin Combination in CHO Cell Lines - Al-Zubairi, Adel Sharaf (Asian Pacific Journal of Cancer Biology, 2017)
Objective: Several natural products are being increasingly used in the treatment of cancer to minimize the adverse side effects of cancer chemotherapy. Zerumbone (ZER), the sesquiterpene derived from Zingiber zerumbet Smith, has been reported to have an in vitro anticancer effects against various human tumour cells as well as in vivo against a number of induced malignancies in mice. Previously we have reported the genotoxic effects of ZER in vitro against CHO cell lines. Material and Method: The aim of this study was to investigate the genotoxic effects of the combination of ZER along with cisplatin in CHO cells. Two cytogenetic endpoints were used, namely Chromosomal Aberrations assay (CA) and Micronucleus test (MN). Both cytogenetic endpoints were performed without any metabolic activation. Result: ZER treated cultures showed the significant increase in the frequency of the chromosome aberrations and MN induction. In CA assay, marked changes have been observed after co-treatment of CHO cell lines with different concentration of ZER along with 5 µM Cisplatin when compared to ZER treatment alone, suggesting a possible synergistic genetoxic effects. Whereas, treatment of CHO cell lines with different concentrations of ZER along with 2.5 µM Cisplatin was found to reduce chromosomal aberrations, suggesting an antagonistic genotoxic effect. On the other hand, in MN induction test, co-treatment of CHO cell lines with both 2.5 µM and 5 µM Cisplatin and different concentration of ZER found to reduce the genotoxic effects compared to the 2.5 µM and 5 µM Cisplatin alone suggesting an antagonistic genotoxic effect. Conclusion: The genotoxic effects of combined low concentrations of Cisplatin with different concentrations of ZER could have an antagonist genotoxic potential in vitro in CHO cell lines.